The Information Content of Share Repurchase Programs - Grullon, Gustavo; Michaely, Roni (Journal of Finance, 2004)
ABSTRACT Contrary to the implications of many payout theories, we find that announcements of open‐market share repurchase programs are not followed by an increase in operating performance. However, we find that repurchasing firms experience a significant reduction in systematic risk and cost of capital relative to non‐repurchasing firms. Further, consistent with the free cash‐flow hypothesis, we find that the market reaction to share repurchase announcements is more positive among those firms that are more likely to overinvest. Finally, we find evidence to indicate that investors underreact to repurchase announcements because they initially underestimate the decline in cost of capital.